Sejahtera: Falsafah Melayu yang Terpinggir - Ratna Roshida Ab Razak; Ahmad Nasir Mohd Yusoff; Nur Ayuni Mohd Isa; Muhammad Hafeez Zakaria (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2022)
Abstract: Prosperity as a Malay life concept based on local wisdom, needs to continue to be empowered to become a guide to ensure true happiness in life. The objective of this paper is to explore the true meaning of well-being, based on its practice in Malaysian society, especially the Malay race itself, as well as a discussion about the concept and its application in life, especially as found in education, as outlined in the National Education Philosophy. Prosperity can be considered as mental health resulting from the balance between the three main components of human events. Prosperity in this context is the application of the values ??of Malaysian society which is seen as an act of being human, who loves oneself, God, others and nature. Prosperity is an ability in Malay culture that expresses happiness, tranquility and peace. Failure to apply the concept of prosperity in society, at all levels, will invite issues related to manners or morals. This study uses a content analysis approach involving secondary data from the literature study conducted. The qualitative data collected were analyzed descriptively. This paper will focus on personal well-being which involves the balance between the three main components of human existence. It is important to understand how Prosperity affects the lives of every individual at all levels. Keywords: prosperity, philosophy, malay